“Tekenscanner”: a novel smartphone application for companion animal owners and veterinarians to engage in tick and tick-borne pathogen surveillance in the Netherlands - Jongejan, Frans (Parasit Vectors, 2019)
BACKGROUND: The engagement of companion animal owners into the process of collecting epidemiological data can be facilitated through smartphone applications. In April 2018, the “tekenscanner“ (Dutch for tick scanner) app was launched with the aim of engaging pet owners and veterinarians to record ticks removed from their pets and submit these ticks for identification and pathogen testing. Tick-borne pathogens identified in ticks removed from dogs and cats during the first 6 months after the app was launched in the Netherlands are reported. METHODS: The tekenscanner app was used to record the geographical coordinates of ticks removed from dogs or cats onto a map of the Netherlands. A barcode was assigned to each tick for the easy tracking of each submission to our laboratory for taxonomic identification. Thereafter, DNA extracted from the ticks was PCR amplified, subjected to reverse line blot hybridization (RLB) and screened for a broad range of tick-borne pathogens. Results were added to the same app, usually within 2 weeks after the submission of each tick. RESULTS: The app was downloaded 5591 times and resulted in the collection of 1273 georeferenced and barcoded ticks, with a peak submission in May and June of 2018. There were 1005 ticks collected from 406 dogs and 268 ticks collected from 111 cats. Ixodes ricinus was the predominant species (90.0%), with all stages found on dogs as well as on cats. Ixodes hexagonus (7.3%) female and nymphal ticks were also identified on both hosts, whereas adults of Dermacentor reticulatus (2.4%) and Rhipicephalus sanguineus (0.2%) were exclusively found on dogs. Nearly 15% of the ticks recovered from dogs carried one or more pathogens, whereas 13.8% of the ticks removed from cats were infected. Ixodes ricinus collected from dogs contained Borrelia spp. (1.9%), Babesia spp. (0.7%), Anaplasma phagocytophilum (1.3%), “Candidatus Neoehrlichia mikurensis” (2.9%) and Rickettsia helvetica (7.3%). Ixodes ricinus recovered from cats were infected with Borrelia spp. (1.9%), Babesia spp. (0.4%), A. phagocytophilum (1.9%), “Ca. Neoehrlichia mikurensis” (2.6%) and R. helvetica (6.7%). Ixodes hexagonus ticks (n = 93) were not infected. Dermacentor reticulatus ticks, found only in autumn, were infected with Rickettsia raoultii (16 %) and A. phagocytophilum. Three R. sanguineus, on dogs from France and the USA imported into the Netherlands, were all negative. CONCLUSIONS: The tekenscanner app is a versatile tool to use for submission of ticks and facilitated the fast feedback of test results. Community engagement through the app is suitable for identifying hotspots for ticks and tick-borne pathogens and provided an early warning system for exotic ticks invading the Netherlands.